Legal Protection of the Commune's Own Tasks in Meeting the Collective Needs of the Community as far as a Municipal Marketplace is Concerned on the Ground of Polish Infractions' Law (Lex localis - Journal of Local Self-Government, 2020)
One of the commune's own tasks is to meet the collective needs of the community. The most important issue from this perspective is the place designated for commerce. The commune may designate such a place on on the territory owned or managed by it. This designated place is called the market, which is every place where the sale is carried out. The regulations in force in Poland show some inconsistency in the approach to sales conducted in places other than shops. On the other hand, the use of the municipal market entails payment of the market fee, the objective scope of which raises doubts.  Sale outside the designated place constitutes an infraction punishable by a fine. Its object of protection is public order and peace. The act consists in conducting sales activity. It may be committed by anyone, both intentionally and unintentionally. The offender is subject to punishment even in the case of a one-off, small sale, but it is possible to waive the penalty.